Formulasi Sediaan Kombinasi Simplisia Daun Katuk, Daun Kelor, Dan Jahe Sebagai Minuman Instan - W Wirasti; ST Rahmatullah; Ainun Muthoharoh (Universitas Muhammadiyah Pekajangan Pekalongan, 2021)
Daun Katuk, Daun Kelor dan Jahe merupakan bahan alam dari tanaman yang telah bayak dimanfaat kan oleh masyarakat. Daun Katuk telah diketahui berguna untuk melancarkan air susu ibu, daun Kelor mengandung senyawa-senyawa yang sanygat bermanfaat untuk meningkatkan gizi, sedangkan Jahe dengan kandungan senyawa kimianya terutama gingerol berguna untuk meningkatkan imunitas. Tujuan penelitian ini adalah memformulasi simplisia daun katuk, daun kelor dan jahe menjadi minuman instan yang dapat menyehatkan tubuh. Metode pembuatan simplisia dengan mengeringkan bahan basah di oven pada suhu 50oC dan metode formulasi ketiga simplisia dengan metode granulasi. Parameter penelitian yang digunakan adalah waktu larur, kadar air, warna, aroma, rasa, kemasan, dan khasiat. Hasil dari penelitian ini adalah waktu larut < 2 menit, kadar air simplisia daun katuk, daun kelor dan jahe berturut-turut adalah 3,5%, 3,5% dan 4%, sedangkan kadar air sediaan instannya sebesar 4%. Hasil Uji kesukaan terdiri dari warna hasil menarik, aromanya harum, rasanya enak, kemasan sangat menarik dan khasiat baik. Kesimpulan dari formulasi minuman instan kombinasi daun katuk, daun kelor dan jahe memenuhi syarat SNI dan hasil uji kesukaan (uji hedonik) adalah suka, menarik dan berkhasiat.. Kata kunci; Daun Katuk, Daun Kelor, Jahe, minuman instan, suka The Combination dosage Formulation of Saurapus Leaf Simplicia, Moringa Leaves, and Ginger as an Instan Drink Sauropus leaves, moringa leaves and ginger are natural ingredients from plants that have been used by many people.Sauropus leaves are known to be useful for breastfeeding, Moringa leaves contain compounds that are very useful for improving nutrition, while ginger with its chemical compounds, especially gingerol, is useful for increasing immunity. The purpose of this study was to formulate the simplicia of sauropus leaves, moringa leaves and ginger into instant drinks that can nourish the body. The method for making simplicia is by drying the wet material in an oven at 50oC and the third formulation method for simplicia is the granulation method. The research parameters used were elusive time, moisture content, color, aroma, taste, packaging, and properties. The results of this study were the dissolving time < 2 minutes, the water content of the simplicia of sauropus leaves, moringa leaves and ginger were 3.5%, 3.5% and 4%, respectively, while the water content of the instant preparations was 4%. The favorite test results consist of attractive color results, fragrant aroma, good taste, very attractive packaging and good properties. The results of this study were the dissolving time <2 minutes, the water content of the simplicia of sauropus leaves, moringa leaves and ginger were 3.5%, 3.5% and 4%, respectively, while the water content of the instant preparations was 4%. The favorite test results consist of attractive color results, fragrant aroma, good taste, very attractive packaging and good properties. The conclusion from the formulation of instant drink combination of sauropus leaves, moringa leaves and ginger meets SNI requirements and the results of the hedonic test are liking, attractive and efficacious Keywords: Sauropus leaves, moringa leaves, ginger, instant drinks, like